Analisis Produktivitas Tenaga Kerja Dinas Kependudukan Kabupaten Ende terhadap Pelayanan Masyarakat - Mbene, Maria Aurelia; Djata, Baltasar Taruma; Penu, Yustina Paulina (JURNAL EQUILIBRIUM, 2022)
This study aims to find out how the productivity of the Population Service workforce is towards community services at the Ende Regency Population Service Office. Collecting data in this study are observation, interviews and documentation. This research uses a type of qualitative research with the analysis technique used, namely productivity with the Objective Matrix (OMAX) method with criteria for working hours and the products produced. The steps using the OMAX method are determining criteria, determining performance, determining realistic productivity values, determining weights, scores and values, determining productivity indices and determining performance indicators. The results showed that the productivity of the population service workforce towards community services at the Ende Regency Population Service office from April to December fluctuated (up and down). The highest DISPENDUK labor productivity value is in September which is at level 10 and the lowest productivity value is in April which is at level 0. Labor productivity indicators in this study are indicators of hours worked and products produced. The results of the study show that the public services of the Ende Regency Population Service in making KTPs, KKs and birth certificates are not yet responsive to the interests of the community as service users. Based on field observations, many complaints from the people of Ende Regency are related to the services provided by employees or employees of the population service which can lead to fights between employees and the community.